Wavelet analysis to decompose a vibration simulation signal to improve pre-distribution testing of packaging. (August 2016) - Griffiths, K.R.; Hicks, B.J.; Keogh, P.S.; Shires, D.
Abstract: In general, vehicle vibration is non-stationary and has a non-Gaussian probability distribution; yet existing testing methods for packaging design employ Gaussian distributions to represent vibration induced by road profiles. This frequently results in over-testing and/or over-design of the packaging to meet a specification and correspondingly leads to wasteful packaging and product waste, which represent 15bn per year in the USA and €3bn per year in the EU. The purpose of the paper is to enable a measured non-stationary acceleration signal to be replaced by a constructed signal that includes as far as possible any non-stationary characteristics from the original signal. The constructed signal consists of a concatenation of decomposed shorter duration signals, each having its own kurtosis level. Wavelet analysis is used for the decomposition process into inner and outlier signal components. The constructed signal has a similar PSD to the original signal, without incurring excessive acceleration levels. This allows an improved and more representative simulated input signal to be generated that can be used on the current generation of shaker tables. The wavelet decomposition method is also demonstrated experimentally through two correlation studies. It is shown that significant improvements over current international standards for packaging testing are achievable; hence the potential for more efficient packaging system design is possible. Highlights: Overcome limitations of current packaging testing regimes. Wavelet decomposition to create superposed components of different kurtoses. Simulation signal that is non-stationary and has a non-Gaussian distribution. Significant improvements over current international standards for packaging testing. Validated against time replication studies for the onset and progression of scuffing.